A relação entre o prescrito e o real no discurso jurídico de destituição do poder familiar - Peters, Ellen Beatriz de Oliveira (2006)
This work aims to make analyses between the prescription and the real in the forensic speech and dismay the ideologies that characterize this relationship. The focus is based on a process, filed in the forum in a city of São Paulo state, observing the veredict of accusation that children were treated badly and where abandoned by their parents. The focus to be analyses is based discursive-enunciative especially from studies Maingueneau (1987, 1997) and specially the ergonomics (Guérin et al. 1997, 2001). The analyses accours between Linguistic where the discursive related (Maingueneau, 2002) and intertexto (Santa anna, 2000) and ergonomical notions prescribed and real, from studies about work and the concept of ideology (Chauí, 1987, 2004). The analyze could show that the relationship between prescription and real accours through interdiscurso and related discourse and the ideologies that exceeded were two. The first about the pattern in the society that says that children should be raised by their families, oven though they face financial problems. It is not possible, it is advisable that children live in a boarding, house provided with the minimum necessary for than with the real family where there are careless and no money. The other considers poverty itself, the real reason that parents abandon their children